2015
DOI: 10.4172/2153-2435.1000e184
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Bleeding in Children can have Many Causes

Abstract: Acute gastrointestinal bleeding in children is a common emergency. Gastrointestinal bleeding may involve any part of the digestive tract from mouth to anus. Causes of gastrointestinal bleeding in children are multiple and can be grouped according to the involved portion of the digestive tract and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Also, bacterial infections, especially infection with Helicobacter pylori can cause peptic ulceration resulting in pediatrics’ GI bleeding ( 13 ). The results of studies have shown that the most common cause of upper GI bleeding in newborn infants and children younger than 2 years are maternal blood ingestion, and gastritis or stress ulcers, respectively ( 10 , 18 , 19 ). Mallory-Weiss tear was also more prevalent in older children ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, bacterial infections, especially infection with Helicobacter pylori can cause peptic ulceration resulting in pediatrics’ GI bleeding ( 13 ). The results of studies have shown that the most common cause of upper GI bleeding in newborn infants and children younger than 2 years are maternal blood ingestion, and gastritis or stress ulcers, respectively ( 10 , 18 , 19 ). Mallory-Weiss tear was also more prevalent in older children ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%